The Olfactory Bulb in Companion Animals—Anatomy, Physiology, and Clinical Importance - Rui Alvites; Abby Caine; Giunio Bruto Cherubini; Justina Prada; Artur Severo P. Varejão; Ana Colette Maurício (Brain Sciences, 2023)
The Olfactory Bulb is a component of the Olfactory System, in which it plays an essential role as an interface between the peripheral components and the cerebral cortex responsible for olfactory interpretation and discrimination. It is in this element that the first selective integration of olfactory stimuli occurs through a complex cell interaction that forwards the received olfactory information to higher cortical centers. Considering its position in the organizational hierarchy of the olfactory system, it is now known that changes in the Olfactory Bulb can lead to olfactory abnormalities. Through imaging techniques, it was possible to establish relationships between the occurrence of changes secondary to brain aging and senility, neurodegenerative diseases, head trauma, and infectious diseases with a decrease in the size of the Olfactory Bulb and in olfactory acuity. In companion animals, this relationship has also been identified, with observations of relations between the cranial conformation, the disposition, size, and shape of the Olfactory Bulb, and the occurrence of structural alterations associated with diseases with different etiologies. However, greater difficulty in quantitatively assessing olfactory acuity in animals and a manifestly smaller number of studies dedicated to this topic maintain a lack of concrete and unequivocal results in this field of veterinary sciences. The aim of this work is to revisit the Olfactory Bulb in companion animals in all its dimensions, review its anatomy and histological characteristics, physiological integration in the olfactory system, importance as a potential early indicator of the establishment of specific pathologies, as well as techniques of imaging evaluation for its in vivo clinical exploration.